2018
DOI: 10.14419/ijet.v7i4.38.27540
|View full text |Cite
|
Sign up to set email alerts
|

Halal Cosmetic Products: Do Knowledge and Religiosity Affect Consumers’ Attitude and Intention to Use?

Abstract: The goal of this research is to examine the effect of knowledge and religiosity on consumers' attitude towards Halal cosmetic products. Furthermore, the influence between consumers' attitude and their intention to use Halal cosmetic products is also explored. The Partial Least Square-Structural Equation Modelling (PLS-SEM) approach supported by Smart-PLS 2.0 was employed to evaluate the hypothesized model. This study conveys a strong message to cosmetic companies, particularly the producers, retailers, and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 14 publications
3
14
1
1
Order By: Relevance
“…In other words, grasping the concept of Halal is insufficient in the Halal food industry; it must be followed by the practice of permissible acts, rules and laws, as well as the possession of knowledge of the circular current that must be observed in light of recent technological breakthroughs. This result contradicts the conclusions of earlier studies such as those by Mohd Suki and Mohd Suki (2018) and Santhanam and Hartono (2003), who obtained findings that the knowledge aspect was of substantial importance. The present study’s results also contrast with those of Muhammad Haziq et al (2015), which found the practice of legal operations in the Halal food sector is based on Halal executives’ scientific knowledge as well as their knowledge of Islam, meaning that those executives had a proper focus on the established Halal assurance system.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In other words, grasping the concept of Halal is insufficient in the Halal food industry; it must be followed by the practice of permissible acts, rules and laws, as well as the possession of knowledge of the circular current that must be observed in light of recent technological breakthroughs. This result contradicts the conclusions of earlier studies such as those by Mohd Suki and Mohd Suki (2018) and Santhanam and Hartono (2003), who obtained findings that the knowledge aspect was of substantial importance. The present study’s results also contrast with those of Muhammad Haziq et al (2015), which found the practice of legal operations in the Halal food sector is based on Halal executives’ scientific knowledge as well as their knowledge of Islam, meaning that those executives had a proper focus on the established Halal assurance system.…”
Section: Discussioncontrasting
confidence: 99%
“…Existing religious knowledge and practice are the key determinants and pillars of Halal management organisations (Muhammad Haziq et al, 2015). A high level of knowledge relating to Halal aspects, including knowledge of the ways and means of compliance with the processing, preparation and nutritional support, is required to increase performance (Mohd Suki and Mohd Suki, 2018;Muhammad Haziq et al, 2015). And organisations that possess a strong ability to use their embodied knowledge system experience significant growth in their performance (Santhanam and Hartono, 2003).…”
Section: Knowledgementioning
confidence: 99%
“…Any information that consumers had related to a product was called product knowledge (Sumarwan, 2014). Such relevant information referred to experiences and facts that consumers had (Suki & Suki, 2018). Product knowledge consists of two categories; product and brand.…”
Section: Knowledgementioning
confidence: 99%
“…Some researchers who studied halal cosmetics suggested that consumers' attitudes did not positively influence purchase intention (Ahmed et al, 2019;Aisyah, 2017;Marmaya et al, 2019). However, some others have found a significant correlation between consumers' attitude and their purchase intention (Abd Rahman et al, 2015;Briliana & Mursito, 2017;Khan & Azam, 2016;Suki & Suki, 2018). Knowledge positively…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia becomes a sleeping giant who is waking up pretty quickly now. Muslim consumers are faced with a wide selection of products and services that are provided in stores, including those of halal and non-halal products (Suki & Suki, 2018). The halal cosmetics industries are gaining the attention of the world now because Muslims feel peace by consuming halal products in every part of their life (Ali, Halim, & Ahmad, 2016).…”
Section: Introductionmentioning
confidence: 99%